Hirschsprung disease with Edward syndrome: A rare association: A case report. (July 2021) - Shrestha, Bibek Man; Shrestha, Diwan; Shrestha, Suraj; Bist, Anil; Kharel, Sanjeev; Koirala, Dinesh Prasad
Abstract: Introduction and importance: Edward's syndrome (ES) occurs as a result of trisomy of chromosome 18 and is associated with multisystem congenital anomalies. The association of ES with various gastrointestinal malformations but Hirschsprung disease (HD) is well documented. Case presentation: A female infant on her 5th day of life presented with episodes of bilious vomiting along with abdominal distension and no passage of stool. The child had a small head and prominent occiput, low set abnormal ears, small jaw, upturned nose, widely spaced eyes, small neck with widely spaced nipples, clenched hands with overlapping fingers, flexed big toe, and prominent heels. Clinical discussion: Edward syndrome is associated with multisystem congenital abnormalities of which gastrointestinal abnormalities make up the most part. The condition can be identified by fetal ultrasound screening. Surgical correction of associated congenital anomalies at different times along with lifelong supportive management is important. Conclusions: Edward syndrome can present as Hirschsprung disease as a part of associated gastrointestinal Malformation. Often, early identification and termination of the pregnancy in antenatal life can reduce the suffering. Surgical correction of associated anomalies along with supportive care forms the cornerstone of management. However, the prognosis remains poor. Highlights: Association of Edward syndrome (Trisomy 18) with Hirschsprung disease is still not clear. Although prognosis is poor, surgical correction of associated anomalies along with supportive care is the crucial in management.